The enhancement of water and energy conservation through condensed water reclamation for evaporative cooling towers - Leung, Yiu-Kuen; Cheng, Ka Wai Eric (Frontiers in Water, 2024)
Although environmental groups have declaimed the application of greywater to alleviate water consumption, the progress of condensed water implementation for high-rise buildings was still sluggish. As greywater demands wastewater treatment before any application, the novelty of this study was to demonstrate the direct use of condensed water in an existing cooling water system without wastewater treatment. Considering there is barely any practical case study research to unveil the water-energy nexus in reclaiming condensed water for evaporative cooling tower systems, this research has signified that condensed water is a simple and low-budget application for water conservation and energy saving. Given that the condensed water possesses an intrinsic impurity-free property, the water-saving potentials have been amplified to the most tolerable total dissolved solids (TDS) of system water. Furthermore, it is beneficial that water quality control ameliorated the operating working conditions, the system performances were improved, and then less power was consumed. By getting rid of the wastewater treatment, consolidating the feasibility of practical direct-use application, and its sustainability for water and energy saving, this research may revive the attention of green building claimers to expedite its implementation and tie in the green building design. The condensed water derived from the electric ventilation system was reclaimed as an alternative water source for cooling without extra power consumption, which was ideal for concentration dilution and beneficial to descaling. An evaporative cooling system consumes tons of water, and the water losses are necessarily compensated by fresh water; this process occurs gradually over time and progressively escalates the TDS with time, which evocates water scale formations. Although the bleed-off (BO) that discharges the impurity-laden system water effectively lowers the TDS, it is not a water conservation measure, and the chemical effluent poses environmental hazards. The higher cycles of concentration (CoC) reduce the frequency of BO and sustain the full efficacy of antiscaling chemicals. Whenever water scales appear as a resistance of heat transfer deposit on the heat exchangers, the heat management capability is diminished and energy efficiency drops. The water and energy saving enhancement method was accomplished by reclaiming the condensed water and setting higher CoC.